Pengaruh Bauran Pemasaran Terhadap Loyalitas Pengguna Jasa Melalui Kepuasan Pada Kantor Notaris Lusi Djuwita,SH - Djuwita, Lusi (STIE AUB Surakarta)
Object of this study is the notary's office Lusi Djuwita,SH., located at Jalan Raya Solo-Sragen Km.11,Kebakkramat,Karanganyar.This study aim to analyze the influence of marketing mix consist of product,place,promotions,price,people,process,and customer service to service user loyalty through satisfication at notary's office Lusi Djuwita,SH.Keywords: marketing mix,product,place,promotion,price,people,process,customer service,satisfaction,loyalty.